Comparison of CT in patients with cerebral ischaemia with or without non-rheumatic atrial fibrillation. European Atrial Fibrillation Trial and Dutch T I A Trial Study Groups. Issue 2 (August 1995) - van Latum, J; Koudstaal, P J; Kappelle, L J; van Kooten, F; Algra, A; van Gijn, J
Abstract : In an attempt to distinguish between the CT characteristics of strokes of presumed cardioembolic origin and strokes caused by arterial disease, a comparison was made between the baseline CT of two prospective cohorts of patients with transient ischaemic attack or minor ischaemic stroke, with (n = 985) or without (n = 2987) non-rheumatic atrial fibrillation (NRAF). Of the patients with NRAF 54% had evidence of cerebral infarction v 41% of the controls (patients with sinus rhythm (SR); odds ratio (OR) 1.7; 95% confidence interval (95% CI) 1.4-1.9). Patients with NRAF more often had multiple infarcts (OR 1.4; 95% CI 1.1-1.8), and more often infarcts that were not related to current neurological symptoms (OR 1.5; 95% CI 1.2-1.8). For symptomatic infarcts, patients with NRAF more often had cortical end zone infarcts (OR 3.1; 95% CI 2.6-3.8) and cortical border zone infarcts (OR 1.9; 95% CI 1.3-2.9) than patients with SR. Conversely, symptomatic small deep infarcts (lacunae) were more often seen in patients with SR (OR 3.9; 95% CI 2.8-5.4). Multivariate analyses showed that all these findings were independent of differences in baseline characteristics between the two study groups. The CT characteristics overlapped and did not allow a reliable distinction between cardioembolic and atherosclerotic causes of stroke in patients with NRAF.